γδ T Cells in HIV Disease: Past, Present, and Future - Pauza, C. David; Poonia, Bhawna; Li, Haishan; Cairo, Cristiana; Chaudhry, Suchita (Frontiers in Immunology, 2015)
Human immunodeficiency virus type 1 (HIV) dysregulates γδ T cells as part of an immune evasion mechanism. Nearly 3 decades of research defined the effects of HIV on γδ T cells and how this impacts disease. With highly effective antiretroviral therapy (ART) providing virus suppression and longer survival, we expected a return to normal for γδ T cells. This is not the case. Even in patients with CD4 T cell reconstitution, normal γδ T cell levels and function are not recovered. The durable damage to Vδ2 T cells is paralleled by defects in NK, CD8 T cells and dendritic cells. Whether these consequences of HIV stem from similar or distinct mechanisms is not known and effective means for recovering the full range of cellular immunity have not been discovered. These unanswered questions receive too little attention in the overall program of efforts to cure HIV this disease. Approved drugs capable of increasing Vδ2 T cell function are being tested in clinical trials for cancer and hold promise for restoring normal function in patients with HIV disease. The impetus for conducting clinical trials will come from understanding the significance of γδ T cells in HIV disease and what might be gained from targeted immunotherapy. This review traces the history and current progress of AIDS-related research on γδ T cells. We emphasize the damage to γδ T cells that persists despite effective virus suppression. These chronic immune deficits may be linked to the comorbidities of AIDS (cancer, cardiovascular disease, metabolic disease and others) and will hinder efforts to eradicate HIV by cytotoxic T or NK cell killing. Here, we focus on one subset of T cells that may be critical in the pathogenesis of HIV and an attractive target for new immune-based therapies.